PENGARUH PENDIDIKAN PELATIHAN DAN PEMANFAATAN TEKNOLOGI TERHADAP KINERJA GURU SMP DI KABUPATEN SIDRAP - Indrayani Indrayani; Nurul Aulia; Arwin Arwin (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Organizing training for teachers can be a form of management efforts in schools to be able to improve and develop knowledge and skills for teachers to become teaching staff who have superior competencies so that they can provide the best education for students. This study aims to analyze the effect of the variable Education Training (X1) and Technology Utilization (X2) on Teacher Performance (Y) in public junior high school teachers in Sidrap Regency. This research was conducted at the Department of Education and Culture, especially in SMPN 1, 2, 3, and 5 Pangsid by distributing questionnaires to 90 respondents, where the data were analyzed using multiple linear regression by performing the coefficient of determination test technique, correlation coefficient test, t-test, and test. F by using SPSS application software. The results of this study partially show that Educational Training (X1) and Utilization of Technology (X2) each have a positive and significant effect on Teacher Performance (Y). The results of the research simultaneously show that X1 and X2 together have a significant effect on Y, while the correlation coefficient test (R) shows a value of 0.786 which means that it is moderately correlated, and the coefficient of determination test (R Square) shows 61.8%